2023
DOI: 10.46827/ejse.v9i1.4629
|View full text |Cite
|
Sign up to set email alerts
|

Parental Participation Practices as Precursors of Pupils’ Early Reading Literacy Skills Achievement Kiambaa Sub-County, Kiambu County, Kenya

Abstract: The purpose of this study was to investigate ways in which parents are involved in their children's education as precursors of early literacy acquisition of children. The study used the Hoover-Dempsey and Sandler Parental Model as its theoretical lens. The study employed a descriptive survey design. Data was collected through questionnaires and a reading assessment checklist for children. Public and private primary schools included in the study were selected through stratified sampling criteria comprising 12% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The reviewed study focused on only one aspect of parental involvement, lacking knowledge on the other levels of parental engagement as described by Joyce Epstein's model, unlike the current study, which looked at different levels of parental involvement, bridging this gap in the literature. Osabinyi and Ouko (2023) designed a study to investigate the effect of parents' involvement in their children's education on the development of their children's early reading skills in Kiambu County, Kenya, employing a descriptive survey design. The outcomes of learners' preliminary literacy abilities in elementary school were found to be affected by parental involvement.…”
Section: Empirical Studies and Knowledge Gapsmentioning
confidence: 99%
“…The reviewed study focused on only one aspect of parental involvement, lacking knowledge on the other levels of parental engagement as described by Joyce Epstein's model, unlike the current study, which looked at different levels of parental involvement, bridging this gap in the literature. Osabinyi and Ouko (2023) designed a study to investigate the effect of parents' involvement in their children's education on the development of their children's early reading skills in Kiambu County, Kenya, employing a descriptive survey design. The outcomes of learners' preliminary literacy abilities in elementary school were found to be affected by parental involvement.…”
Section: Empirical Studies and Knowledge Gapsmentioning
confidence: 99%
“…Research has shown a linear and positive relationship between parental involvement in school activities, like attending parent-teacher conferences, PTA meetings, classroom visits, and volunteering for schools and their children's reading and math performance. High expectations and continual support for children to learn, and reading activities at home, and, as a result of this, parents' engagement with their children during the pre-school period has been found to play a key role (Osabinyi, 2023).…”
Section: Introductionmentioning
confidence: 99%